Apigenin ameliorates postoperative inflammation and accelerates wound healing in a rat model of perianal abscess by targeting the JAK1/STAT3 pathway in macrophages - Dai, Ruixue; Cao, Liangliang; Ren, Jiahui; Liu, Jingru; Zhu, Kexin; Chen, Peidong; Yao, Weifeng; Zhao, Xuelong; Bao, Beihua; Zhang, Li (Frontiers in Immunology, 2026)
BackgroundExcessive inflammation mediated by macrophages impedes wound healing following surgical drainage of perianal abscess, a common yet challenging condition in colorectal surgery. Cayratia japonica ointment (CJO) has shown clinical efficacy, but its active immunomodulatory constituents and mechanisms remain unclear.MethodsWe evaluated the anti-inflammatory effects of seven CJO-derived flavonoids in LPS-stimulated RAW264.7 macrophages. Skin pharmacokinetics were assessed in mice, and therapeutic efficacy was tested in a rat postoperative perianal abscess model. Molecular mechanisms were investigated via Western blot, RT-qPCR, and molecular docking.ResultsPharmacokinetic analysis revealed that apigenin exhibited the highest transdermal exposure among all detected components. In vitro, apigenin significantly suppressed LPS-induced production of IL-6, TNF-α, and IL-1β in RAW 264.7 cells. In vivo, apigenin treatment markedly reduced serum levels of these pro-inflammatory cytokines, attenuated inflammatory cell infiltration, and promoted collagen deposition at the wound site. Mechanistically, apigenin downregulated both the phosphorylation and total protein levels of JAK1 and STAT3, suggesting functional modulation of the JAK1/STAT3 signaling pathway.ConclusionApigenin may contribute to observed biological effects of CJO that promotes wound healing by attenuating macrophage-driven inflammation through potential modulation of the JAK1/STAT3 signaling pathway, offering a promising natural immunomodulator for postoperative wound management.